2020
DOI: 10.1038/s41598-020-66146-y
|View full text |Cite
|
Sign up to set email alerts
|

Vault changes after cyclopentolate instillation in eyes with posterior chamber phakic intraocular lens

Abstract: posterior chamber phakic intraocular lens (pioL) implantation is a common option for correcting moderate-to-high ocular refractive defects. Because this pIOL is implanted on ciliary sulcus, the distance between the back surface of the pIOL and the anterior surface of the crystalline lens, that it is known as vault, should be measured in different conditions to ensure the technique's safety. Cyclopentolate is a drug that dilates the pupil and relaxes accommodation (cycloplegia). It is often used for different o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This agreed on other studies on IPCL as Bianchi GR et al 2019 and Bianchi GR et al 2019 (14,15) . AS-OCT was used for angle evaluation with ICL as Singh R et al 2020 who implanted ICL in 32 eyes with 3 months follow-up and resulted in stable angle narrowing in the follow-up period and Gargallo-Martinez, B et al 2020 who studded vault of ICL by OCT (16,17) .…”
Section: Resultsmentioning
confidence: 99%
“…This agreed on other studies on IPCL as Bianchi GR et al 2019 and Bianchi GR et al 2019 (14,15) . AS-OCT was used for angle evaluation with ICL as Singh R et al 2020 who implanted ICL in 32 eyes with 3 months follow-up and resulted in stable angle narrowing in the follow-up period and Gargallo-Martinez, B et al 2020 who studded vault of ICL by OCT (16,17) .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Wan et al [ 16 , 17 ] on 82 myopic eyes implanted with Visian ICL used 3 instruments: AS-OCT, Oculus Pentacam and UBM for assessment of ACD and central vault for 3 months. They demonstrated that AS-OCT measurements were higher while Pentacam measurements were lower than UBM measurements.…”
Section: Discussionmentioning
confidence: 99%
“…When the eye exposed to light, the pupil will constrict. When the PD changes, the vault will change accordingly [ 5 9 ]. The safety vault should take into consideration of the change with the light.…”
Section: Introductionmentioning
confidence: 99%